2017
DOI: 10.1002/mnfr.201700721
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Interacts with Markers of Adipose Tissue Browning, Insulin Action and Plasma Acetate in Morbid Obesity

Abstract: Gut microbiota composition is linked to adipose tissue browning and insulin action in morbidly obese subjects, possibly through circulating acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 45 publications
2
75
1
1
Order By: Relevance
“…In a study with NAFLD patients, acetate was found increased in circulatory level and fecal level, analyzed by NMR. This increase was correlated with the reduction of the abundance of several bacterial species as Ruminococcus, Coprococcus, and F. prausnitzii [58]. HFD-induced obesity and IR in rats is associated with increased plasma concentration of acetate metabolized by the gut microbiota measured with GS-MS [33].…”
Section: Acetatementioning
confidence: 83%
“…In a study with NAFLD patients, acetate was found increased in circulatory level and fecal level, analyzed by NMR. This increase was correlated with the reduction of the abundance of several bacterial species as Ruminococcus, Coprococcus, and F. prausnitzii [58]. HFD-induced obesity and IR in rats is associated with increased plasma concentration of acetate metabolized by the gut microbiota measured with GS-MS [33].…”
Section: Acetatementioning
confidence: 83%
“…Composition of intestinal microbiota is linked to adipose tissue browning and insulin action in morbidly obese individuals, possibly via circulating acetate [167]. In grade III obese, the firmicutes RA strain was negatively correlated with serum glycated hemoglobin (HbA1C) and serum triglycerides concentrations and was positively associated with brown adipocyte markers such as the PR domain containing 16 (PRDM16), uncoupling protein 1 (UCP1), and type II iodothyronine deiodinase in subcutaneous adipose tissue.…”
Section: Acetatementioning
confidence: 99%
“…As previously described, cross-sectional studies showed negative associations between acetate and fasting insulin in obese women [9]. Similarly, in morbidly obese subjects, a negative association with HOMA-IR and a positive association with insulin sensitivity were observed [10]. Furthermore, acute distal colonic acetate infusions increased fat oxidation and improved metabolic profile in overweight/obese men [6,7].…”
Section: Discussionmentioning
confidence: 68%
“…Recently, a study reported that acetate produced in the distal colon contributes significantly to systemic acetate concentrations in men [8]. In line with this, cross-sectional analyses in patients with obesity have shown positive associations between high circulating acetate and insulin sensitivity indices [9,10]. In women, plasma acetate correlated negatively with fasting and postprandial insulin concentrations [9].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation